The Role of Storytelling to Improve Early Childhood Speaking Skills - Handayani, Mila Sri; Siagian, Togar; Khayati, Ni'matul; Hayati, Kulsum Nur (Journal of Language, Literature and Teaching, 2024)
Early childhood is a critical period for language development, laying the foundation for future communication skills. Storytelling has long been recognized as a powerful tool in language acquisition, particularly in enhancing speaking abilities. This paper examines the role of storytelling in improving speaking skills among early childhood learners. It explores the theoretical underpinnings of storytelling as a pedagogical approach and its alignment with early childhood development theories. Furthermore, the paper reviews empirical studies and evidence supporting the effectiveness of storytelling in fostering oral proficiency in young children. Additionally, it discusses practical strategies and techniques for integrating storytelling into early childhood education curricula. The findings suggest that storytelling not only enhances speaking skills but also promotes language comprehension, vocabulary acquisition, and socio-emotional development. The paper concludes with implications for educators and recommendations for future research in this field.